(3GdQhV GdhVGM aj JgGfi GdCaQGMs
(3ChdgG (B:s
(3cdGe GdeOjM ef GdebOe jeOM GdMGVQjf , jbhd jMchG djdI SYjOI YfOeG QCjJ Ggd GdCOH HOhQ GdceGd deG WdHJhfi Gdjce CJjJ ddYH hGdJaQjM hbJ GdNjGd s
(3BNQgG (B:s
(3eMeO LGfG HGdgOi hGdHTGjQ jTaY dfG jhe GdMSGH ef fGQ Lgfe jG fGUQ s
(3HChdgG agQS ddTYQ HNW MOjK eZGjQ hHBNQ UaMGJgG JYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B49 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3TYQ JjehQ (B785) s
Keywords: (3GdCOHs